Some Physical Properties of the Grains of Two Cultivars of Sorghum (Sorghum bicolor (L.) Moench) - Abdalla, Eman Abdu; Ismail , Mohamed Ayoub; Mohamed, Abdelmoniem Elamin (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted at the Department of Agricultural Engineering, Faculty of Agriculture, University of Khartoum and the Food Processing Research Center, Shambat, Sudan. The study was carried out with the objective of determining some physical properties of two local grain sorghum cultivars that affect design of processing machines, storage structures and processes. The studied of physical properties included grain size, shape, 1000 grain weight, hectoliter (test) weight, hardness, bulk density, true density and porosity. These properties were determined at initial moisture content and the results were analyzed using the t-test. The results showed that the the two cultivars were significantly different in size, shape and hardness, while they were not significantly different with respect to hectoliter (test) weight, 1000 grain weight, bulk density, true density and porosity. The studied cultivars of grain sorghum do not require different designs of milling machines, grain hoppers, aeration, drying machines and storage structures, while they differ with respect to design of sieve separators, harvesting, sizing, grinding machines and in calculating surface area and volume of grains which are important during modeling of grain drying, heating and cooling processes